Retrospective multicenter matched case–control study on the risk factors for intussusception in infants less than 1 year of age with a special focus on rotavirus vaccines – the German Intussusception Study. Issue 10 (2nd October 2020) - Oberle, Doris; Hoffelner, Marcus; Pavel, Jutta; Mentzer, Dirk; Barth, Immanuel; Drechsel-Bäuerle, Ursula; Keller-Stanislawski, Brigitte
ABSTRACT: Studies associate rotavirus vaccination with intussusception. In Germany, a retrospective multicenter matched case–control study was performed to identify risk factors for intussusception with a special focus on rotavirus vaccines. Children with place of birth and residence in Germany who had been treated for intussusception from 2010 to 2014 and who had been less than 1 year old at the time of intussusception were recruited. Case report forms were independently validated by two pediatricians according to the criteria of intussusception defined by the Brighton Collaboration (BC). Cases with the highest diagnostic certainty (level 1) were matched with population-based controls by age, gender, federal state, and place of residence. Information on vaccine exposures originated from vaccination certificates. One hundred and sixteen cases were matched with 272 controls. A significantly increased adjusted odds ratio (aOR) for intussusception (5.74, 95% CI: 1.51–21.79) was detected in individuals immunized with rotavirus vaccine dose 1 prior to symptom onset as compared to non-exposed individuals. Age at the start of the rotavirus immunization series did not modify the risk of intussusception. The odds for intussusception were not increased postdose 2 and 3 as well as any dose. One further risk factor for intussusception, family history of intussusception (aOR 3.26, 95% CI 1.09 − 9.77) was identified. Breastfeeding was found to have a protective effect (aOR 0.54, 95% CI 0.33 − 0.88). Rotavirus vaccine dose 1 was associated with a 5.7-fold increased risk to develop intussusception regardless of age at immunization whereas the overall risk for intussusception in the first year of life was not increased.